Advanced trauma life support course for medical students. A new era? - Vassiliu, Panteleimon; Mavrogenis, Andreas; Theos, Christos; Koulouvaris, Panagiotis; Massalis, Ioannis; Geranios, Angelos; Bartsokas, Christos; Gerazounis, Michael; Tepetes, Konstantinos; Kamparoudis, Apostolos; Stergiopoulos, Spyros; Stavropoulos, Michael; et al. (Frontiers in Surgery, 2022)
Introduction Trauma represents a major public health issue and one of the leading causes of death and disability worldwide. A systematic approach for dealing with trauma patients was facilitated through ATLS course, which has been a milestone in trauma care. Our new concept of an ATLS course for medical students was set in motion in 2015. Our aim was to make medical students familiar with trauma patients interactively, through a program such as ATLS, and here we present the results of this endeavour. Methods A two-days ATLS-Medical Student (MS) course was offered from November 2015 to July 2018. Retrospective analysis of the data gathered over a three-month period through online questionnaires was performed. 261 newly qualified medical doctors were interviewed and evaluated the ATLS course they had before graduation. Results After the course, the vast majority of medical students (251 MS; 96.16%) felt more capable of managing the severely injured patients and a 58% of students felt that the medical services they offered were better due to the ATLS training. Regarding the educational fee, 56.7% of the students reported that the fee of 100 euro was proper. Discussion The interactive format of the course, unlike more traditional methods of teaching, has been endorsed by medical students. Though they lack clinical experience that does not prohibit them from acquiring more specialised/specific knowledge and even excel. Most of the students improved their skillset either in theoretical knowledge, practical skills or even in the emotional component of the course i.e., confronting a severely injured patient. The extension of the program to all Greek Medical Schools and its re-evaluation were decided. Conclusion The advantage of having trauma trained doctors at the beginning of their careers is evident. For that reason, extension of the program to all Greek Medical Schools and re-evaluation were decided.